Long-term high-altitude exposure influences task-related representations in visual working memory - Bao, Xiaohua; Zhang, Delong; Li, Xiaoyan; Liu, Ming; Ma, Hailin (Frontiers in Neurology, 2023)
Objective Human working memory is impaired when individuals are exposed to high altitudes, however, whether the capacity of visual working memory is affected remains unclear. This study combined a lateralized change detection task and event-related potentials analysis to explore changes in visual working memory capacity among individuals who emigrated from a low-altitude environment to Tibet (a high-altitude environment). Materials and methods Thirty-five college students were recruited from Tibet University as the high-altitude (HA) group, and thirty-six low-altitude (LA) students were enrolled from South China Normal University (sea level) as the LA group. We measured participants' contralateral delay activity (CDA) under different memory loads. Results ERP component analysis showed that both the HA and LA groups reached an asymptote at memory load four. However, the contralateral and ipsilateral activity of the HA and LA groups shows different patterns. The results showed a significantly larger contralateral activity for the LA group than for the HA group at memory load one (p = 0.04, Cohen's d = 0.52) and load three (p = 0.02, Cohen's d = 0.61). Additionally, we found marginally larger contralateral activity at memory load four for the LA group (p = 0.06, Cohen's d = 0.47), but not at memory load two (p = 0.10) or load five (p = 0.12). No significant differences were observed for ipsilateral activity. In addition, we observed that the HA group performed larger ipsilateral activity than contralateral activity under each memory load, compared with the LA group. Conclusion These findings demonstrated that the attentional resource of long-term HA exposure is more captured by task-irrelevant information, potentially due to impaired inhibitory control, which makes it difficult for them to exclude the interference of task-irrelevant information.